Setting Up and Providing Telepsychiatry Services in India - Ali, Furkhan (Indian J Psychol Med, 2020)
The exponential growth of technology in the past few decades has benefitted the healthcare sector. Telemedicine is a newer advancement which is making healthcare affordable and more accessible to the needy in recent times. This article discusses how to set up telepsychiatry services, the procedure of telepsychiatry consultation, how to record and maintain the electronic health records, the potential challenges, ethical and legal aspects concerning telepsychiatry while ensuring the good practice guidelines, medical ethics, patient rights, and the minimum requirements as established by the Information Technology Act and the telemedicine practice guidelines (TPG) 2020 issued by the Indian Medical Council.